Non-Verbal Predication in Ancient Egyptian - Loprieno, Antonio; Müller, Matthias; Uljas, Sami (The Mouton Companions to Ancient Egyptian, 2017)
The Egyptian language, with its written documentation spreading from the Early Bronze Age (Ancient Egyptian) to Christian times (Coptic), has rarely been the object of typological studies, grammatical analysis mainly serving philological purposes. This.